Study Of The Influence Of The Operational Parameters On The Removal Of Cod, Bod And Colour Of An Industrial Wastewater Treatment Plant - Mustafa, Aidil Azami (Universiti Sains Malaysia, 2018)
The research attempts to study the influence operational parameters for industrial wastewater treatment plant. Industrial production such as medical device company create large quantities and varieties of wastewater that are causing serious environmental pollution. Latex wastewater is one of the industrial wastewater generated from manufacturing product that originated from latex processing material. The pH of latex wastewater is about 3.88 and it was in acidic condition. The COD, BOD and Color of latex wastewater were 1093mg/L, 48.8mg/L and 1751PtCO respectively. There are several treatment processes to treat industrial wastewater and it generally divided into three stages of treatment which is physical, chemical and biological treatment. In this study, five selected points in the latex wastewater treatment plant was monitored and the removal efficiencies was compared between physical, chemical and biological treatment. Physical, chemical and biological treatment of the selected treatment plant was rubber trap, coagulation and flocculation and biological treatment using Effective Microorganism. The average removal efficiency of COD, BOD, Colour and TSS for biological treatment are 79%,39%,74% and 78% respectively. Then, chemical treatment using coagulation and flocculation method and ferric chloride as coagulant able removed 56% of COD and 28% of BOD in latex wastewater. During coagulation and flocculation treatment processes, 53% of TSS and 38% of Colour have removed. The most efficient treatment is biological treatment using (EM). The result also shows the studied parameter of treated effluent follows the standard B discharge for industrial effluent.